Hashimoto’s Thyroiditis and Female Fertility: Endocrine, Immune, and Microbiota Perspectives in Assisted Reproduction—A Narrative Review - Emilia Cristina Popa; Laura Maghiar; Teodor Andrei Maghiar; Ilarie Brihan; Laura Monica Georgescu; Bianca Anamaria Toderaș; Liliana Sachelarie; Anca Huniadi (Biomedicines)
Hashimoto’s thyroiditis is the most prevalent autoimmune thyroid disorder, and it disproportionately affects women of reproductive age. Its impact on fertility and assisted reproductive technologies [ART] has become an area of growing clinical interest. Thyroid autoimmunity can influence female reproductive health through multiple interconnected mechanisms, including subtle thyroid hormone imbalances, reduced ovarian reserve, altered endometrial receptivity, and dysregulated immune responses. Subclinical hypothyroidism and the presence of anti-thyroid antibodies have been linked to increased miscarriage risk and reduced success rates in ART, particularly in intracytoplasmic sperm injection (ICSI) cycles. Although levothyroxine supplementation is widely used, its benefits in euthyroid women remain uncertain. Recent studies suggest that gut microbiota may modulate immune function and affect fertility outcomes among women with autoimmune thyroid conditions. This narrative review synthesizes findings from a broad literature base of over 40 peer-reviewed publications published between 2010 and 2025, with 30 of the most relevant and methodologically robust studies selected for detailed analysis. The review integrates clinical, endocrine, immunological, and microbiome-related perspectives. The evidence supports the need for personalized fertility management in women with Hashimoto’s thyroiditis and highlights directions for future research into immune and microbiota-targeted therapies.